Appraisal of Highway Tunnels Construction on the Active Railroad Tunnel Operational Reliability in the City of Sochi. (2017) - Frolov, Y.S.; Konkov, A.N.; Svintsov, E.S.
Abstract: The article highlights a set of researches performed to ensure the operational reliability of the railway tunnel with the highway tunnels constructed above it in the city of Sochi. The tunnel intersection on the highway includes 2 parallel tunnels with the length of 544, 1 and 557, 8 meters. Engineering-geological conditions are classified as complex: three tunnels on the problem area are located in the low and reduced strength mudstone with the inclusion of lenses and interlayers of Sandstone. According to the results of the theoretical research, limit value of the strength and deformation parameters of railway tunnel lining were determined. Stress-strain state of lining in nearly real-life conditions is determined. The work program for permanent automated geodetic monitoring of the highway tunneling allowed us to obtain information about possible changes in the technical state of railway tunnel lining. The complex of performed measures allowed ensuring the safety of construction work of the highway tunnel and continuous movement of Tuapse-Adler trains passing through central areas of Sochi.